Clinical Reasoning: A 74-year-old woman with bilateral foot pain and a palmar rash. (7th February 2017) - Wynn, DonRaphael P.; Donigan, Jessica M.; Tkach, Aleksander
Abstract : A 74-year-old woman with a history of asthma, Crohn disease, and osteoporosis presented with acute onset, constant sharp pain in the dorsal and plantar aspects of her bilateral feet. She endorsed associated paresthesias, but denied weakness. Several weeks after the onset of the pain, she developed pruritic palmar erythema. She denied dry eyes, dry mouth, or having had a rash like this before, but did endorse scaling on her hands following her biannual injection of denosumab for osteoporosis.